Clustal Omega for making accurate alignments of many protein sequences. (30th October 2017) - Sievers, Fabian; Higgins, Desmond G.
Abstract: Clustal Omega is a widely used package for carrying out multiple sequence alignment. Here, we describe some recent additions to the package and benchmark some alternative ways of making alignments. These benchmarks are based on protein structure comparisons or predictions and include a recently described method based on secondary structure prediction. In general, Clustal Omega is fast enough to make very large alignments and the accuracy of protein alignments is high when compared to alternative packages. The package is freely available as executables or source code fromwww.clustal.org or can be run on‐line from a variety of sites, especially the EBIwww.ebi.ac.uk .